Marine mites (Acari: Hydrachnidia) of the Mediterranean Sea: Descriptions of two new species, key for identification and future prospects - Pešić, Vladimir; Durucan, Furkan; Zawal, Andrzej (Zootaxa, 2019)
This paper provides a current overview of the diversity of the marine water mite family Pontarachnidae of the Mediterranean Sea. The checklist includes ten species from two genera, i.e. Litarachna Walter, 1925 and Pontarachna Philippi, 1840. Two species i.e., Litarachna muratsezgini sp. nov. and Pontarachna turcica sp. nov. from the Gulf of Antalya (Levantine Sea, Turkey), are described as new for science. Moreover, the key for the identification of Mediterranean Pontarachnidae species and a brief discussion on the current gaps and future prospects of our knowledge of this important but neglected component of the marine meiofauna are given.